Mapping of Corrosion Sites in Advanced Gas-cooled Reactor Fuel Cladding in Long Term Pond Storage - Ronald N. Clark (2018)
This thesis aims to investigate sites where corrosion initiates on an austenitic stainless steel used to encapsulate advanced gas-cooled nuclear reactor fuel when in long term pond storage and subsequently provide insight into what happens when corrosion propagates. The combination of both a critical temperature and radiation dose within the reactor core may lead to very small quantities of this stainless steel becoming sensitised. The first chapter is a discussion on the literature and past study on the subject. Within the second chapter, analysis of the stainless steel in an as-received format is undertaken, and is relevant, given that only a very small quantity of cladding may be rendered sensitised. This chapter includes an investigation into Cl- concentration and temperature dependence.The third chapter focuses on identifying the initiation points of localised intergranular corrosion (IGC) in freely corroding and perturbed environments. An in-situ time-lapse microscopy and scanning vibrating electrode technique investigation are used in conjunction with post corrosion microscopy to study areas affected by IGC. The fourth chapter describes a higher resolution approach to investigating the initiation point of IGC. A scanning Kelvin probe force microscope is used to map the surfaces for areas in which corrosion may occur, while an atomic force microscope was used to provide high resolution images of tens of grains undergoing in-situ IGC. The aim of the final chapter is to provide an insight into reducing corrosion rates using an NaOH pre-treatment. NaOH is used in two different concentrations to study the effect on the free corrosion and breakdown potentials (Ecorr and Eb) on as-received and sensitised 20/25/Nb.This study will provide a scientic backbone that the industry may use to target areas of further research, helping provide ongoing safe storage of spent nuclear fuel in the UK.